VISUAL AND SYMBOLIC REPRESENTATION FORMING: A CASE OF RELATIONAL UNDERSTANDING ON ELEMENTARY STUDENT - Mohammad Faizal Amir; Mahardika Darmawan Kusuma Wardana; Devi Usfuriah (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study investigates the process of forming Anna’s visual and symbolic representations at each stage of the development of relational understanding in solving fractional problems. This study focuses on Anna (pseudonym), a 4th-grade elementary school student in Sidoarjo Regency. Anna possessed the complete process of forming visual and symbolic representations and is the only student who is able to provide logical arguments to support her answer. This research is qualitative in nature with a case study. The results were analyzed using the Miles and Huberman model by reducing the data, presenting the data, and drawing conclusions. Results show the process of forming Anna’s visual and symbolic representations at each stage of the development of relational understanding in solving fractional problems. Anna has difficulty forming visual representations because she has weaknesses in the concept of fractional equations and fractional operations. This resulted in the process of forming symbolic representations and procedural knowledge that tends to be rote. These findings indicate that Anna developed a relational understanding, namely, a conceptual understanding of fractions. The process of forming a visual representation is the main basis before the formation of a symbolic representation.